Effects of Climatological and Socioeconomic Factors on Chronic Poverty - Jairo, Michael Ndwiga (European Scientific Journal, ESJ, 2019)
Poverty remains one of the key development goals for developing countries. Achieving this goals may be far-fetched given the increasing vagaries from climate change. This paper sought to estimate the effect of climate and weather variability on chronic poverty using household panel data for Kenya. Using Chamberlain random effects probit model with control function, the paper found that weather variability reduces the likelihood of a household falling into chronic poverty. Household heads with post-secondary education were less likely to fall into chronic poverty and those who earned off-farm income and had access to credit facilities had lower probability of falling into poverty as compared to those who did not. The findings suggests the need to devise policies on climate mitigation in order to cushion households from devastating effects of weather variability and to create awareness through dissemination of climate information in easy and widely accessible formats.